2017
DOI: 10.4314/sokjvs.v15i3.13
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of <i>Toxoplasma gondii</i> infection in slaughtered pigs in Makurdi, Nigeria

Abstract: Toxoplasma gondii, can infect warm blooded animals, birds as well as humans. This study was designed to determine the seroprevalence of Toxoplasma gondii infection in slaughtered pigs in Makurdi, Nigeria. A crosssectional study was designed in which 181 blood samples were collected from two pig slaughterhouses in Makurdi (Wurukum and Railway) from September to December 2014. Sera were harvested and stored at -20 :C until required for processing. Indirect ELISA test kit (ID-Vet, France) was used to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These findings are consistent with many other studies. 20,[37][38][39]24 However, there has been a report of significantly increased anti-T. gondii IgM seropositivity with age in pregnant women. 24 The relationship between age and T. gondii infection as observed in the current study disagrees with some other reports.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with many other studies. 20,[37][38][39]24 However, there has been a report of significantly increased anti-T. gondii IgM seropositivity with age in pregnant women. 24 The relationship between age and T. gondii infection as observed in the current study disagrees with some other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Tissues of infected chickens are also considered a common source of infection for cats [4]. Several studies have reported varying seroprevalence of T. gondii in chickens and pigs [5][6][7], as well as detection of T. gondii DNA in chicken and pork meat products [8,9], raising concerns of possible risk to humans. Bioassays remain the most sensitive means of detecting Toxoplasma cysts in animal tissues [10], but these methods are laborious, time-consuming and are poorly adapted to the screening large numbers of samples [10].…”
Section: Introductionmentioning
confidence: 99%